IMPROVİNG THE CAPACİTİES OF TRAVEL AGENCİES WİTH PRODUCT AND MARKET DİVERSİFİCATİON STRATEGİES - Ömer Çoban, (PEOPLE: International Journal of Social Sciences, 2025)
There are various studies in the literature that point out the importance of product and market diversification for destinations and tourism businesses. However, there are limited studies on the obstacles that tourism businesses face during product and market diversification. Therefore, the research has attempted to reveal what these obstacles are through data collected from travel agencies and their stakeholders using the interview technique. It has been determined that the barriers to the product and market diversification processes of businesses are specialization, lack of operational experience, lack of qualified personnel, possible operational costs and insufficient public support. In order to eliminate the aforementioned barriers within the scope of the research, suggestions have been developed for travel agencies and stakeholders who have an impact on their activities.